1986
DOI: 10.1001/archotol.1986.03780050088017
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Delayed Postoperative Malignant Hyperthermia

Abstract: \s=b\ Malignant hyperthermia (MH) may be triggered by exposure to commonly employed anesthetic agents and muscle relaxants, and often manifests itself during the period of anesthesia. Delayedonset MH occurring one to four hours postoperatively has been described in isolated case reports. A case of delayedonset MH occurred 11 hours following routine tonsillectomy and adenoidectomy. The patient demonstrated tachypnea, tachycardia, hyperthermia, and metabolic acidosis. Prompt intravenous administration of dantrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…MH reactions can become apparent in PACU and, where trigger agents have been involved, all events with one exception 23 have developed within one hour of transfer to PACU [24][25][26][27] . Reported reactions following trigger-free anaesthesia are few and in general, mild [4][5][6][28][29][30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…MH reactions can become apparent in PACU and, where trigger agents have been involved, all events with one exception 23 have developed within one hour of transfer to PACU [24][25][26][27] . Reported reactions following trigger-free anaesthesia are few and in general, mild [4][5][6][28][29][30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of the delayed type of malignant hyperthermia are tachypnea, tachycardia, hyperthermia and metabolic acidosis etc. [6]. But our patient showed all these symptoms of the delayed type of malignant hyperthermia except metabolic acidosis.…”
Section: Discussionmentioning
confidence: 64%
“…That was the first reported case in which the delayed type of malignant hyperthermia occurred in a WHS patient even following surgery. It has also been reported that the delayed type of malignant hyperthermia can occur even 11 hours after the completion of a surgical procedure [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Improved anaesthetic and surgical techniques 14 have contributed to this policy, improving the cost-effectiveness of day-case surgery and limiting escalating healthcare costs. MH reactions in the postoperative period have been well described [15][16][17][18][19] . A review of the suspected cases of postoperative MH in the North American Malignant Hyperthermia Registry from 1987 to 2005 found that, of 528 possible cases, only ten were considered 'likely' MH reactions 18 .…”
Section: Discussionmentioning
confidence: 99%